Speech and language therapy assessment of patients on the 2-week wait head and neck cancer referral pathway: evidence and opinion following a pilot study. Issue 3 (June 2021) - Occomore-Kent, Louise; Slade, Suzanne
Abstract : Purpose of review: Spiralling numbers of patients are being referred on the two-week wait (2WW) head and neck cancer referral pathway. Only a small proportion are found to have cancer. There is a call for change in the management of these referrals, particularly following coronavirus. Allied health professionals (AHPs) are being encouraged by the NHS to extend their clinical practice to address increased demand. Speech and Language Therapists (SLTs) may offer a solution to some of the 2WW pathway's challenges. Recent findings: Recent evidence highlights problems with the pathway and reasons for change. Hoarse voice is consistently found to be the most common presenting symptom. Emerging evidence suggests SLTs can extend their scope of practice to manage new hoarse voice referrals. A pilot project is described. Outcomes from this and other ongoing studies explore efficacy and investment required to make this proposal an achievable prospect for the future Summary: The management of 2WW referrals on the head and neck cancer pathway needs to change. Preliminary findings suggest SLTs working within the context of the multidisciplinary team can safely extended their role to improve management of these patients. Professional role outline, recognition, guidance, and training framework are needed.